Nonspecific Urethritis(NSU) or Non-Gonococcal Urethritis(NGU),The Biggest Problem In Sexually Transmitted Diseases(STD) A Literature Study - Soedarmadi, Soedarmadi (Universitas Gadjah Mada, 1975)
Not adequately realized by the practicing physician is that at least half of the cases of urethritis seen in practice are not due to gonococcus and will not respond to penicillin, but will respond to tetracyclin.The etiology of NSU is not clear yet, but the role of infective agent (or agents) is clear. The diagnosis is made by exclusion.Despite the lack of agreement concerning the aetiology, the treatment is relavely simple, and tetracycline is the drug of choice.